Pulsed focused ultrasound can improve the anti-cancer effects of immune checkpoint inhibitors in murine pancreatic cancer. Issue 180 (7th July 2021) - Mouratidis, Petros X. E.; Costa, Marcia; Rivens, Ian; Repasky, Elizabeth E.; ter Haar, Gail
Abstract : Pulsed high-intensity focused ultrasound (pHIFU) uses acoustic pressure to physically disrupt tumours. The aim of this study was to investigate whether pHIFU can be used in combination with immune checkpoint inhibitors (ICIs) to enhance survival of tumour-bearing animals. Murine orthotopic pancreatic KPC tumours were exposed both to a grid of pHIFU lesions (peak negative pressure = 17 MPa, frequency = 1.5 MHz, duty cycle = 1%, 1 pulse s −1, duration = 25 s) and to anti-CTLA-4/anti-PD-1 antibodies. Acoustic cavitation was detected using a weakly focused passive sensor. Tumour dimensions were measured with B-mode ultrasound before treatment and with callipers post-mortem. Immune cell subtypes were quantified with immunohistochemistry and flow cytometry. pHIFU treatment of pancreatic tumours resulted in detectable acoustic cavitation and increased infiltration of CD8 + T cells in the tumours of pHIFU and pHIFU + ICI-treated subjects compared with sham-exposed subjects. Survival of subjects treated with pHIFU + ICI was extended relative to both control untreated subjects and those treated with either pHIFU or ICI alone. Subjects treated with pHIFU + ICI had increased levels of CD8 + IFNγ + T cells, increased ratios of CD8 + IFNγ + to CD3 + CD4 + FoxP3 + and CD11b + Ly6G + cells, and decreased CD11c high cells in their tumours compared with controls. These results provide evidence that pHIFU combined with ICI may have potential for use in pancreatic cancer therapy.